Enhancing Speaking Skills through Small-talk2Me AI Tool in the English Language Learning Process among High School Students at a Public Institution in Riobamba City, the school year 2023-2024. - Martínez Durán, Luis Mauricio (2024)
This study aimed to explain the effectiveness of the SmallTalk2Me AI tool in improving English-speaking skills among Third Bachillerato students. The research encourages reflection on the benefits of the SmallTalk2Me AI tool as an innovative strategy that integrates language learning with technology, targeting to enhance learners' speaking skills. A quasi-experimental design was utilized, incorporating both quantitative and qualitative approaches. Data were gathered using various instruments, including pre-and post-tests and a questionnaire that pointed to understanding the students' perceptions regarding using this tool. The results reveal that the implementation of the SmallTalk2Me AI tool had a positive effect on students' speaking skills. Significant improvements were found in aspects such as fluency, grammar, and vocabulary, with the most notable enhancement observed in fluency, between the pre-and post-tests. The findings suggest that the SmallTalk2Me AI tool is a valuable resource for improving speaking skills, offering students opportunities to practice in an interactive environment and increase their confidence in oral communication. Finally, the study shows that the SmallTalk2Me AI tool effectively supports the students to remain focused, engaged, and eager to practice speaking.